Warisan budaya: Menggali pengaruh budaya jepang dalam identitas nasional Indonesia pasca pendudukan - Effendy, Syazani Azmy (Maliki Interdisciplinary Journal, 2025)
The Japanese occupation of Indonesia (1942-1945) was a period of profound cultural and social change. The Japanese not only replaced Dutch rule, but also implemented policies that affected various aspects of people’s lives. In this context, Japan introduced a new education system oriented towards military needs and propaganda, aiming to shape a national identity that suited Japanese interests. On the other hand, while there were some positive impacts of the Japanese occupation, such as improved infrastructure and wider access to education, many negative impacts also emerged. The exploitation of Indonesia’s natural resources for Japanese war interests caused environmental damage and reduced the availability of resources for local communities. In addition, human rights violations that occurred during the occupation, including forced labor and suppression of resistance, left deep wounds in the nation’s collective memory. This research aims to explore the influence of Japanese culture during the occupation and its impact on Indonesian society.